2014
DOI: 10.1186/1129-2377-15-33
|View full text |Cite
|
Sign up to set email alerts
|

Headache yesterday in Europe

Abstract: BackgroundSurveys enquiring about burden of headache over a prior period of time (eg, 3 months) are subject to recall bias. To eliminate this as far as possible, we focused on presence and impact of headache on the preceding day (“headache yesterday”).MethodsAdults (18-65 years) were surveyed from the general populations of Germany, Italy, Lithuania, Luxembourg and the Netherlands, from a work-force population in Spain and from mostly non-headache patient populations of Austria, France and UK. A study of non-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
5
14
0
1
Order By: Relevance
“…Asking participants about headache yesterday offers the unique chance to (almost) eliminate recall bias. Currently, only two studies have been published applying this approach in adults [ 20 , 21 ]. In the present study, pupils with headache yesterday showed several differences from those with headache last year but not yesterday: headache frequency was higher, duration longer, intensity more severe and use of abortive headache medication more common.…”
Section: Discussionmentioning
confidence: 99%
“…Asking participants about headache yesterday offers the unique chance to (almost) eliminate recall bias. Currently, only two studies have been published applying this approach in adults [ 20 , 21 ]. In the present study, pupils with headache yesterday showed several differences from those with headache last year but not yesterday: headache frequency was higher, duration longer, intensity more severe and use of abortive headache medication more common.…”
Section: Discussionmentioning
confidence: 99%
“…This is the third published analysis of headache yesterday (HY) worldwide, following those in China [ 10 ] and eight countries of Europe [ 7 ], and the first in Russia. It is of some interest to know the proportion of a population afflicted by headache on any day, but the true value of this population-based enquiry lies in its almost complete detachment from the recall errors to which traditional burden-of-headache surveys are so strongly subject.…”
Section: Discussionmentioning
confidence: 99%
“…Some have also estimated headache-attributed burden, and those assessing socioeconomic impact have employed questionnaires such as the Migraine Disability Assessment (MIDAS) instrument [ 5 ] or its derivative, the Headache-Attributed Lost Time (HALT) questionnaire [ 5 , 6 ]. The former, and in its original form (HALT-90) also the latter, depend upon enquiry relating to the three months prior to the interview, an approach subject to the limitations and errors (and possible biases) of recall over such a long period [ 7 ]. The consequences of these limitations, errors and possible biases need to be considered, and an alternative approach that allows this is enquiry into headache occurring on the day before the interview (“headache yesterday”; HY).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all three earlier published studies of HY, similar internal consistency has been seen between reported HY and prediction of 1-day headache prevalence based on estimated 1-year prevalence and recalled frequency during the preceding 3 months [1517]. What was underestimated in recall over 3 months was the productivity loss, which was calculated at population level in Karnataka at only 1.8 % [18])–seemingly a major error.…”
Section: Discussionmentioning
confidence: 56%